Effectiveness Evaluation of quality Management System in Construction Engineering Testing Laboratory Based on Triangle Fuzzy Analytic Hierarchy Process. (May 2019) - Du, Dandan; Song, Xiaosheng
Abstract: At present, there are few evaluations on the effectiveness of the quality management system of the construction engineering testing laboratory in our country. According to the quality management system of the quality management system, a two-stage evaluation structure model of the quality management system effectiveness is established according to the Evaluation criteria for the qualification of the Laboratory. A comprehensive evaluation of the quality management system of a building engineering testing laboratory in Tangshan City was carried out by using triangular fuzzy number analytic hierarchy process (AHP), and the evaluation results were obtained in accordance with the actual situation.